Multiple on-line data collection and processing for radioimmunoassy using a micro-computer system. Issue 5 (May 1980) - Carter, N W; Davidson, D; Lucas, D F; Griffiths, P D
Abstract : A micro-computer system is described which has been designed to perform on-line data capture from up to seven radioisotope counters of different types in parallel with interactive results processing and subsequent transmission to a laboratory computer-based data management system.